واقع استخدام تكنولوجيا السبورة الذكية لدى المعلمين وأثرها على التحصيل العلمي ودافعية التعلم في مادة الرياضيات لدى طلبة معاهد العلوم الإسلامية بسلطنة عمان - جابري، عبد الله حميد سعيد (Kulliyah of Education, International Islamic University Malaysia, 2021)
The study aims at exploring the teachers' use of smart boards and its effects on performance and motivation on Math in the Islamic institutes in Oman. Descriptive and experimental methods were used and it involves all teachers of Islamic institutes. Regarding the study effects on performance and motivation, the sample includes two groups control and experimental group. The control group includes 15 students and the experimental group 15 students as well. All students have been chosen using the purposive method. The study seeks to answer the following questions: To what extent smart boards are used in the Islamic institutes, Are there any statistical differences in grade eleven students' performance in the post test of Math through applying smart board for both control and experimental groups? Are there any statistical differences in grade eleven students' motivation in math in using the smart board? Are there any statistical differences in grade eleven students through the continuous assessment of using the smart board in both the control and experimental groups? What are the challenges that encounter the teachers in using the smart board in the Islamic Institutes; and what are teachers' suggestions in developing using the smart board? The results of the study revealed that there are statistical differences between the two groups in terms of their academic performance and motivation in preference to the experimental group. The study further investigated the challenges teachers faced and the suggestions to develop using the smart board. Based on the study results, it was recommended to train teachers on how to use smart board effectively.